Micromeria fruticosa Induces Cell Cycle Arrest and Apoptosis in Breast and Colorectal Cancer Cells - Waseem El-Huneidi; Naglaa G. Shehab; Khuloud Bajbouj; Arya Vinod; Ahmed El-Serafi; Jasmin Shafarin; Lara J. Bou Malhab; Wael M. Abdel-Rahman; Eman Abu-Gharbieh (MDPI AG, 2020)
Micromeria fruticosa (L.) Druce subsp. serpyllifolia (Lamiaceae) has been used widely in folk medicine to alleviate various ailments such as abdominal pains, diarrhea, colds, eye infections, heart disorders and wounds. A few reports have confirmed different therapeutic potentialities of its extracts, including the anti-inflammatory, gastroprotective, analgesic, antiobesity and antidiabetic activities. This study aimed to investigate the mechanistic pathway of the antiproliferative activity of the ethanolic extract of M. fruticosa on two different cancer cell lines, namely human breast (mammary carcinoma F7 (MCF-7)) and human colorectal (human colon tumor cells (HCT-116)) cell lines. The 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide tetrazolium (MTT) assay, Annexin V-FITC/PI, caspases 8/9 and cell cycle analyses, qRT-PCR and Western blot were used to assess the effect of M. fruticosa on cytotoxicity, apoptosis, cell cycle, cell cycle-related genes and protein expression profiles in MCF-7 and HCT-116. The extract inhibits cell proliferation in a time- and dose-dependent manner. The half-maximal inhibitory concentration (IC50) for both cell lines was found to be 100 μg/mL. Apoptosis induction was confirmed by Annexin V-FITC/PI, that was related to caspases 8 and 9 activities induction. Furthermore, the cell cycle analysis revealed arrest at G2/M phase. The underlying mechanism involved in the G2/M arrest was found to be associated with the downregulation of CDK1, cyclin B1 and survivin that was confirmed by qRT-PCR and Western blotting.